A Study on Vulnerabilities and Threats to Wearable Devices (Journal of The Colloquium for Information Systems Security Education, 2020)
Connected, wearable devices are increasingly being adopted by individuals who want to monitor personal data such as location and vital biometrics, and to receive performance feedbacks and product updates in real time. The quality of life gains these gadgets support for users, and the opportunities they enable for vendors to maintain ongoing relationships with consumers, may backfire if security and privacy are not addressed appropriately. This research explored cybersecurity vulnerabilities, threats, and risks related to wearable devices using the Fitbit smartwatch as a popular example. Analysis focused on the sensors that are integrated into such devices. Understanding how these components work exposed ways they can be exploited, which in turn suggested ways to mitigate potential cyber-attacks on wearable devices. These findings provide a foundation for developing awareness and education, and recommending best practices for wearable devices to balance their functionality and convenience with personal privacy and organizational cybersecurity concerns.
Keywords: wearable devices; vulnerabilities; threats; risk management